Position and Progressivity of Islamic Economic Law in Indonesia - Rara Genta Munggarani Basri Rara; Ade Irma Imamah Ade Irma (JURNAL ILMU SYARIAH, 2025)
Implementing Islamic economics is a necessity, including in Indonesia. The strengthening of Islamic economic law is very important in the implementation of all mechanisms that exist in the Islamic economic system. In Indonesia, the Islamic economy is growing rapidly nowadays, despite some challenges and obstacles remaining. This study aims to determine the position and development of Islamic law in Indonesia with qualitative methods and documentation, and a literature approach. The existence of the Islamic economy is marked by the development of Islamic financial institutions, such as Islamic Banking, and the Islamic Non-Bank Financial Industry (IKNB). Also, there are many improvements in Islamic economic law, such as the DSN MUI fatwa. The formation of DSN is a step efficiency and coordination of scholars in response to issues related to Islamic economic/financial issues, as a law that drives everything in Islamic economic law in Indonesia Keywords: Islamic economic law; Fatwas DSN-MUI; Progressivity and development